About the neuroprotective effects of FK-506, L-carnitine and azathioprine on spinal cord ischemia-reperfusion injury [1] (multiple letters) - (:unkn) unknown (My University, 2004)
[No abstract available]
Keywords: Azathioprine; FK-506; L-Carnitine; Spinal cord ischemia